2019
DOI: 10.1088/1742-6596/1321/3/032032
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effects of Aloe vera peel extract on type 2 diabetic rats

Abstract: Aloe vera is one of many medicinal plants used as hypoglycemic. Higher glucose levels are one of the characteristics of diabetes mellitus. This research aimed to study effectiveness of Aloe vera peel extract on insulin and serum glucose levels of rats with type 2 diabetic. Twenty Wistar rats were induced intraperitoneally using single dose of 65 mg/kg of streptozotocin (STZ) and 230 mg/kg of nicotinamide acid (NA). The rats were divided into control and treatment groups, which was supplemented using 100 mg/kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…18 The current RCD aims to fetch Aloe Vera's tremendous metabolic (serum glucose and triglyceride lowering) effects in diabetes control under the limelight. 19 In the present study, we found that treatment with Aloe Vera whole leaf as well as Aloe Vera gel extracts significantly decreased FBS, HbA1c, and triglycerides with almost similar efficacy to each other as well as to Sitagliptin in male diabetic albino rats. Similar to our work, Ayesha Noor, et.al conducted a study to evaluate the role of Aloe extract in enhancing insulin release from Beta cells of the pancreas in Streptozotocin-induced diabetic Wistar rats and found that Aloe Vera extracts at 300mg/kg/d for three weeks, resulted in normalizing blood glucose and increasing insulin level as well.…”
Section: Discussionsupporting
confidence: 66%
“…18 The current RCD aims to fetch Aloe Vera's tremendous metabolic (serum glucose and triglyceride lowering) effects in diabetes control under the limelight. 19 In the present study, we found that treatment with Aloe Vera whole leaf as well as Aloe Vera gel extracts significantly decreased FBS, HbA1c, and triglycerides with almost similar efficacy to each other as well as to Sitagliptin in male diabetic albino rats. Similar to our work, Ayesha Noor, et.al conducted a study to evaluate the role of Aloe extract in enhancing insulin release from Beta cells of the pancreas in Streptozotocin-induced diabetic Wistar rats and found that Aloe Vera extracts at 300mg/kg/d for three weeks, resulted in normalizing blood glucose and increasing insulin level as well.…”
Section: Discussionsupporting
confidence: 66%
“…more about the clinical use of aloe vera extract as an antidiabetic to treat T2DM. (Christijanti et al, 2019) Aloe vera peel extract given for 28 days had an effect on reducing blood sugar levels in hyperglycemic rats. Various doses are needed in order to obtain an optimal dose of aloe vera bark extract which is useful as a therapeutic drug to reduce blood sugar levels and improve pancreatic histology of hyperglycemic rats (Peniati et al, 2018) Therefore, it is concluded that besides insulin, Aloe vera gel can also be a better choice in controlling blood sugar levels (Qadeer et al, 2019) There was a significant difference in blood sugar levels between before and after administration of aloe vera juice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the high content of calcium in Aloe Vera stimulates beta cells of the pancreas to release insulin and raises hepatic insulin and glycogen concentrations. 21 Aloe Vera safeguards beta cells from destruction and recovers the partly damaged β cells. 22 The present study was so designed to bring Aloe Vera's extremely useful metabolic effects in diabetes control under the limelight.…”
Section: Discussionmentioning
confidence: 99%